Methadone in the Treatment of Neuropathic Pain - Bruno Gagnon; Abdulaziz Almahrezi; Gil Schreier (Pain Research and Management)
BACKGROUND: Methadone, being an N-Methyl-D-Aspartate receptor antagonist, may have a potential role in the treatment of neuropathic pain.